2011
DOI: 10.1021/ja210299g
|View full text |Cite
|
Sign up to set email alerts
|

Structural Role of Counterions Adsorbed on Self-Assembled Peptide Nanotubes

Abstract: Among noncovalent forces, electrostatic ones are the strongest and possess a rather long-range action. For these reasons, charges and counterions play a prominent role in self-assembly processes in water and therefore in many biological systems. However, the complexity of the biological media often hinders a detailed understanding of all the electrostatic-related events. In this context, we have studied the role of charges and counterions in the self-assembly of lanreotide, a cationic octapeptide. This peptide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
51
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(59 citation statements)
references
References 38 publications
6
51
0
2
Order By: Relevance
“…The lines are guides to the eye, and the grey area indicates the region where we experimentally observe crystals. This diagram colligates data from this study and from references [31,37]. NB: The datapoint tagged 0 corresponds to a lanreotide derivative whose lysine side chain has been acetylated.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The lines are guides to the eye, and the grey area indicates the region where we experimentally observe crystals. This diagram colligates data from this study and from references [31,37]. NB: The datapoint tagged 0 corresponds to a lanreotide derivative whose lysine side chain has been acetylated.…”
Section: Discussionmentioning
confidence: 92%
“… (diamonds) and Gobeaux et al . (circles). The ordinate reads the ‘normalized’ hindrance of the modifications, whether it is a chemical modification of the aromatic residue in position 4 (open diamonds), on the aliphatic residue on position 5 (triangles) or a change of counter‐ions (circles).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the molecular bases of tumor response to SSAs are still unclear, although the application of proteomics to this field has led to promising results 60. Finally, the ongoing drug research has shown that LAN – above a critical assembly concentration of 20 mM – spontaneously forms hollow nanotubes when solubilized in pure water 61,62. Moreover, a recent study evaluated the utility of a self nano-emulsifying delivery system for model peptide LAN which provided a protective effect toward thiol–disulfide exchange reactions and can be useful to overcome sulfhydryl barrier of the gastrointestinal tract 63.…”
Section: Resultsmentioning
confidence: 99%
“…After extensive work led by Cherif-Cheikh and Valery et al [19–28], the self-assembly process and liquid crystal structure of lanreotide depot formulation are now well characterized. The process starts with noncovalent peptide dimerization, formation, and growth of an open ribbon and ends with ribbon closure in the shape of a nanotube (Fig.…”
Section: Lanreotide Depot Formulationmentioning
confidence: 99%
“…Most importantly, in vitro experiments have shown that the nanotube assembly is completely reversible. At low lanreotide concentration, the nanotubes slowly disassemble, releasing the active drug [19, 23]. The slow and controlled drug release that starts immediately upon transfer into a dilute solution renders the nanotube formulation an ideal candidate for fast-acting and sustained delivery of lanreotide.
Fig.
…”
Section: Lanreotide Depot Formulationmentioning
confidence: 99%